Pemanfaatan Sampah Sebagai Media Tanam Meningkatkan Pemberdayaan Ekonomi Masyarakat Desa Gempol Sari - Muhammad Dzakwan Rafa; Davina Shafa Fellisa; Meisanti Meisanti (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity is motivated by the increasing volume of household plastic waste that has not been optimally managed, thus potentially polluting the environment. Utilizing inorganic waste, especially used plastic bottles, as a planting medium is a simple solution to reduce pollution while increasing community creativity. This activity aims to increase community knowledge and skills in utilizing used plastic bottles as a useful and economically valuable planting medium container. The Women Farmers Group (KWT) participated in this activity on May 1, 2026 in Gempol Sari Village, Sepatan Timur District, Tangerang Regency, Banten Province. Participatory Action Research (PAR) strategies were used to carry out implementation techniques, which included socialization, training, direct practice, mentoring, and assessment. Pre- and post-activity tests were given and evaluated using Paired Sample T-Tests to assess the activity. After participating in the training, the level of participant understanding increased, in accordance with the results of the activity. Participants' knowledge increased significantly through this exercise, as indicated by a significant increase in their average post-test score from 92.86 to 78.57 (p < 0.05). In addition, participants were able to independently practice making simple planting media from used plastic bottles. This activity has positive implications for increasing environmental awareness and community creativity, as well as supporting economic empowerment and sustainable environmental management efforts.